Dostępność transportowa Uniejowa – ujęcie regionalne - Wiśniewski, Szymon (Biuletyn Uniejowski, 2014)
This article investigates transport accessibility of Uniejów – a small town in Łódź voivodeship. It has been assessed through analysis of transport infrastructure in qualitative and quantitative terms, and effectiveness of public and individual transport in the temporal and economic aspect. All measurements were put in the topological perspective, with reference to the remaining 43 towns of Łódź voivodeship. This enabled identification of the degree of Uniejów’s transport accessibility in the settlement network of the region. Quick, safe and possibly inexpensive transport connections are particularly important for Uniejów because of its spa and recreational function.